Determination of heavy metals deposition from palm oil mill / Noor Azimah Darus and Salwa Adam - Darus, Noor Azimah; Adam, Salwa (2012)
Palm oil mills nowadays will affect the environment as it will produce smoke and fumes in its operation by using palm waste materials like fiber and shell as fuel energy was the main factor contributing to the emission of ash. This ash will fly together with the smoke and known as fly ash. Four radius areas recovered which were north. south, west and east of palm oil mill with five different distances. The objective of this study was to determine the concentration of heavy metal in airborne deposited and soil located at four areas of study (north. south, east and west) of the palm oil mill at FELCRA Nasaruddin Bota Perak which focuses on deposited airborne and soil sampling. The samples were analyzed using the X-Ray Fluorescence (ED-XRF). Overall, the pattern of variation in concentration (mg/kg) of airborne deposited elements in all distance at all direction showed that the highest concentration (mg/kg) were manganese (Mn), zinc (Zn) and iron (Fe). Meanwhile, the lowest concentration (mg/kg) were mercury (Hg) and cobalt (Co). In the soil sample, the pattern of variation in concentration (mg/kg) Of elements at all distance in all direction showed that the highest concentration (mg/kg) were manganese (Mn), Zinc (Zn), vanadium (V) and iron (Fe). Meanwhile, the lowest concentration (mg/kg) were mercury (Hg) and cobalt (Co). The elements concentration in soil accumulation is depended on the fertilizer application, water runoff and soil structure.